A simple modification of the A. nidulans transformation protocol increases the transformation frequency - J A Cockram; Sealy-Lewis (Fungal Genetics Reports, 2000)
After transformation of Aspergillus nidulans with plasmid DNA the transformants are usually incubated at 37C until transformants appear. We have found that pre-incubation of the transformation plates at room temperature for 24h leads to increased transformation frequencies.